Sosialisasi Penggunaan Media Digital dalam Memperkenalkan Alat Transportasi dengan Bahasa Inggris : Canva dan Blooket - Widiawati, Sarovah; Susanthi, Novi Indah; Chairuddin, Irwan; Lesatari, Riza (Jurnal Abdimas Transportasi & Logistik, 2024)
Digital learning media use has been increasing since COVID-19 pandemic, with Canva and Blooket being among the most used ones. Both of them were used in the classroom to introduce transportation tools in English to teachers at TPQ Al-Kahfi Bogor. The purpose of this activity is to introduce Canva and Blooket.  Furthermore, this socialization activity was carried out through demonstration and discussion. In addition, this activity was done in hybrid, which was online and offline, and it involved kindergarten and TPQ teachers as the audience. The teachers were introduced to Canva's features for creating interesting learning materials. Blooket, on the other hand, was mainly used for interactive quiz games that can enhance student engagement. Based on the results, it is found that participants felt that this activity was very beneficial in understanding the use of digital media. Moreover, although some teachers are already familiar with Canva and YouTube, Blooket is still new for them. In conclusion, this socialization shows positive results in encouraging the use of more creative digital media, which is expected to improve the quality of learning at TPQ Al-Kahfi. Thus, this activity contributes to the development of educational quality and can serve as a model for other educational institutions.Kata kunci : sosialisasi, Canva, Blooket, pembelajaran bahasa Inggris, alat transportasi